(untitled) (Stavební obzor - Civil Engineering Journal, 2018)
Tunnel invert is a weak section of curved beam on tunnel foundation, and it is easy to break down. Based on the curved beam theory on elastic foundation, the curved beam model of tunnel invert was established, the displacement equation of tunnel invert under external load was deduced, and the formula of settlement of tunnel bottom and the pressure of rock mass was presented. By means of the calculating formula, the distribution law of settlement of tunnel bottom and pressure of rock mass w ere obtained when tunnel bottom was strengthened and not strengthened by high pressure jet grouting pile. The final formula in the paper is precise to predict the settlement of tunnel bottom and pressure of rock mas s, so it is of great value for tunnel design and construction.